Generating Mersenne Prime Number Using Rabin Miller Primality Probability Test to Get Big Prime Number in RSA Cryptography - Dicky Apdilah; Nurul Khairina; Muhammad Khoiruddin Harahap (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2017)
Cryptography RSA method (Rivest - Shamir - Adelman) require large-scale primes to obtain high security that is in greater than or equal to 512, in the process to getting the securities is done to generation or generate prime numbers greater than or equal to 512. Using the Sieve of Eratosthenes is needed to bring up a list of small prime numbers to use as a large prime numbers, the numbers from the result would be combined, so the prime numbers are more produced by the combination Eratosthenes. In this case the prime numbers that are in the range 1500 < prime <2000, for the next step the result of the generation it processed by using the Rabin - Miller Primarily Test. Cryptography RSA method (Rivest - Shamir - Adleman) with the large-scale prime numbers would got securities or data security is better because the difficulty to describe the RSA code gain if it has no RSA Key same with data sender.